Frigidity - Cryle, P. author. aut Link
VI, 317 p.
Keywords: This first major study of a curiously neglected term in the history of sexuality will intrigue students, scholars and enthusiasts alike. The authors take us through a journey across four centuries, showing how notions of sexual coldness and frigidity have been thought about by legal, medical, psychiatric, psychoanalytic and literary writers.